Consensus Assessment on a Metropolitan Railway Project in the Urban Area of Cagliari, Italy: A Case Study of Contingent Valuation - Corrado Zoppi (European Regional Science Association (ERSA), 2001)
Active participation of local civic communities in the planning process implementation not only is a necessary condition for the process effectiveness, but also, and mainly, a fundamental ethical reference point. In other words, a planning process that does not take account of public participation may be not only ineffective, but also it may fail to pursue general welfare. Non-participated planning processes usually imply exclusion or misunderstanding of requirements and needs particularly of those segments of the civic community whose power and voices are low, for economic, social, or cultural reasons, during elections and decision-making struggles. Thus, favoring public participation in planning processes is primarily an ethical imperative and, secondly, a choice that aims to make planning processes effective. Analysis, decision-making, and implementation of planning processes must be built upon a research work that integrates proposals, needs, and expectations of local communities. The development of these processes should recognize and include what local communities express in terms of participation requirements. Recognition and inclusion not only need to be implemented on a case-by-case ba-sis, but also they must be formally established in planning codes as standard procedures of planning implementation. This positive and normative approach is fundamentally based on a sound, continuous, and productive dialectical relationship between public administration and public domain, that must be particularly pursued in the Italian local contexts such as Sardinia, where civic communities are not educated in a culture of participation in public decision-making processes. It is also evident that the outliving of planning as a discipline aimed to the definition and implementation of effective policies for the local communities' livable space organization is strictly connected to a radical change of the points of reference of the behavioral praxes of the different involved stakeholders. This is particularly important with reference to the public administrators, or, at least, to a part of them, since there is no reason to believe that public administrators who aim to perpetuate their positions of political power may be interested to better public involvement in planning processes either qualitatively or quantitatively. Starting from this assumption, this essay summarizes some positions and experiences significant of the importance of radical changes of planning practices, and discusses a case study of consensus assessment on a metropolitan railway project in the urban area of Cagliari, Italy, by means of a contingent valuation methodology.
Keywords: 330